Major flood of 1988 in the Yamuna river upto Delhi (MAUSAM, 1990)
The study of the peak flood during the year 1988 in the Yamuna River up to Delhi Railway Bridge has been made and presented in this paper along with the special features of this flood. The total number of the floods during the yea: 1988 with duration and peak gauge readings are also mentioned in this study.             The present study IS based on the analysis of the rainfall data collected from raingauge stations lying in and around the Yamuna catchment up to Delhi.